Adoption Of Sugarcane Cultivation Technology In Sandy Soil, Purworejo District, Central Java - Kusumaningrum, Arta; Hasanah, Uswatun; Utami, Dyah Panuntun (Agro Ekonomi, 2024)
The efforts to increase agricultural production are expected to year-over-year increase. The aims of this study were 1) to determine the characteristics of farmers in cultivating sugarcane in sandy soil, 2) to determine farmers' adoption of sugarcane plantation cultivation in sandy soil, and 3) to determine the productivity of sugar cane plantations in sandy soil. The research applied descriptive method. The total sample taken was 30 samples who were sugarcane farmers from the sandy soil, Purworejo Regency by purposive sampling. The instrument used was using a Likert scale ranging from strongly agree, agree, undecided, disagree, and strongly disagree. To answer the first objective used descriptive analysis, second, and the third objective used class intervals (low, medium, and high). The results of this study are 1) characteristics of sugarcane farmers on sandy soil in Purworejo Regency are classified as productive, the highest level of education of the farmers is junior high school, the experience of farmers in cultivating sugarcane on sandy soil are > 15 years, the total production of sugarcane are 5- 6 ton, the area of farmer's land are 2-4 Ha, and the productivity level of farmers are 3 - 4 ton/Ha. 2) the adoption rate of sugarcane farmers on the sandy soil of Purworejo Regency are medium, and 3) the level of productivity of sugarcane farmers on the sandy soil of Purworejo Regency is classified as medium productivity. The utilization of coastal land should add compost to increase soil moisture. The seeds that have been certified and have SNI.